Gestión de Riesgos mayores en los talleres, edificio Central y oficinas de Planificación del GAD Provincial de Napo: Plan de Emergencia. - Vargas Andrade, Víctor Alfonso (2012)
The present study establishes the necessary activities for the analysis of institutional risks, reduction of risks and prevention of emergencies, this has been established because of the ignorance that many public and private institutions have, for this reason the SNGR and the fire department are the entities in charge of providing the instructions in everything related to the improvement of the response capacity with which the Provincial GAD of Napo must react. This will lead to the objective established for this study, since, when carrying out a major risk management in every building, the rules will be executed, however, the institution does not have any rules yet, since no study related to institutional risks has been done. For the survey, national methodologies like the evaluation components from the Risk Management National Secretariat and international methodologies like the MESERI, NFPA and others were used. They will be implemented in each one of the facilities to be analyzed, obtaining in this way the results that allow the categorization of areas with major risks, specifically to the workers. The obtained results will tell us clearly the vulnerabilities that the facilities show and they will allow us to present a proposal of improvement that involves the personnel and the facilities, this will allow the implementation of emergency elements as well as to make up brigade members that will be in charge of managing an adverse event in a better way. Finally we will know if the study carried out in the Provincial GAD of Napo helped and if it will assure the physical integrity of the people going to the facilities, explaining clearly the actions to carry out in case of an emergency, this will have to be controlled by people in charge of carrying out future studies by means of an improvement in each one of the processes and activities or simply with training related to the topic and aimed to the whole personnel working in the institution.